New therapeutic approaches in corticosteroid-induced diabetes mellitus in children - Cristina Maria Mihai; Tatiana Chisnoiu (Romanian Journal of Pediatrics)
Corticosteroid-induced diabetes is a significant complication in pediatric patients receiving steroid therapy for various medical conditions. This article reviews the pathophysiology, diagnosis, and management of corticosteroid-induced diabetes in children. Key therapeutic strategies include lifestyle modifications, pharmacologic interventions, and careful monitoring of blood glucose levels. Emphasis is placed on individualized treatment plans tailored to the child's specific needs and underlying condition. The article also discusses the importance of interdisciplinary collaboration among healthcare providers to optimize outcomes and minimize long-term complications. Early recognition and proactive management are critical in improving the quality of life for affected children.